Digital VS Human :` How We`ll Live, Love and Think in the Future - Richard Watson (Amaryllis / Manju Publishing, 2018)
From the author of the international bestseller Future Files comes the one book you need to read to prepare for the world of tomorrow. On most measures that matter, we've never had it so good. Physically, life for humankind has improved immeasurably over the last fifty years. Yet there is a crisis of progress slowly spreading across the world. Perhaps this is due to a failure of vision; in the 1960s we dreamed of flying cars and moon hotels; today what we've ended up with are status updates and cat videos. To a large degree, the history of the next fifty years will be about the relationship between people and technologies created by a tiny handful of designers and developers. These inventions will undoubtedly change our lives, but the question is, to what end? What do we want these technologies to achieve on our behalf? What are they capable of, and - as they transform the media, the economy, healthcare, education, work, and the home - what kind of lives do we want to lead? Richard Watson hereby extends an exuberant invitation for us to think deeply about the world of today and envision what kind of world we wish to create in the future. In a fascinating and accessible way, Digital vs Human examines the possible effects of technology on every area of our lives